PEMODELAN B-SPLINE UNTUK MENGESTIMASI KURVA YIELD OBLIGASI PEMERINTAH KODE FIXED RATE - Nurcahyanti, Tri Meida; Widiharih, Tatik; Warsito, Budi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2019)
Bond is a medium-long term loan agreement that can be handed over, it contains a promise from the issuer to pay rewards in the form of interest on a particular period and paying off the principal debt on the time that has been appointed to the bond buyer. A method to find out the relationship between yield and time to maturity for a type of bond at any given time is illustrated through the yield curve. One of the methods for estimating yield curve is B-spline. The data that used to estimate the yield curve with B-spline model are sourced from Indonesia Stock Exchange, namely Government Bond Trading Report with code FR (Fixed Rate). The data periods used are 9, 16, and 23 November 2018. The best model for estimating the yield curve at any period of the data is linear B-spline model with 6 knots but the knot position is different for every data period. Based on the calculation of MAPE, the ability of the model to predict is very good. Investment with maximum profit based on the estimation of yield curve using B-spline linear model with 6 knot is FR0071.Keywords: bond, yield, yield curve, Government Bond, B-spline